Clinical study of upper abdominal pain in hospitalised patients in medicine unites of a medical college in Dhaka City (Study of 104 cases) - Sardar, MH; Howdar, MAR; Malik, MU; Appolo, AM; Islam, MS; Azad, KAK; Hossain, MM (Journal of Dhaka Medical College, 2012)
DOI: http://dx.doi.org/10.3329/jdmc.v20i2.10538 J. Dhaka Med. Coll. 2011; 20(2): 124-133